Bates' guide to physical examination and history taking - Bickley, Lynn S. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
"The 10th edition of the pre-eminent textbook on physical examination and history taking contains foundational content to guide students' approaches to history taking, interviewing, and other core assessment concepts, as well as fully illustrated, step-by-step techniques that outline correct performance of physical examination. The comprehensive content is intended for high-level nursing education and practice markets, medical students, and related health professions (eg, physician assistants). Text includes head-to-toe assessment and techniques of communication videos."--Jacket
Overview: physical examination and history taking -- Clinical reasoning, assessment, and recording your findings -- Interviewing and the health history -- Beginning the physical examination: general survey, vital signs, and pain -- Behavior and mental status -- The skin, hair, and nails -- The head and neck -- The thorax and lungs -- The cardiovascular system -- The breasts and axillae -- The abdomen -- The peripheral vascular system -- Male genitalia and hernias -- Female genitalia -- The anus, rectum, and prostate -- The musculoskeletal system -- The nervous system -- Assessing children: infancy through adolescence -- The pregnant woman -- The older adult
Includes bibliographical references and index
13
Keywords: Medical history taking; Physical diagnosis; Anamnese (geneeskunde); Lichamelijk onderzoek; Medical History Taking -- methods; Physical Examination -- methods